Autiease kit ultimate comfort and convenience solution / Nor Maslia Rasli Samudin … [et al.] - Samudin, Nor Maslia Rasli; Mohd Fuad, Nurfasihah Haziyah; Ali, Syamimi Wardah; Mohamed Jizad, Farah Yasmin; Dury, Nur Nabilah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Autism spectrum disorder is characterized by challenges with communication, social interactions, sensory sensitivities, and social interactions. These difficulties manifest as anxiety, social isolation, and barriers to performing daily tasks. The current availability of resources may prove inadequate to address the diverse needs of these individuals, leading to a lack of crucial equipment that compromises their autonomy and overall welfare, as well as that of their caregivers. To address these challenges, we propose the development of an “AutiEase Kit” comprising an extensive assortment of specialized tools and resources designed specifically for individuals with autism. It consists of calming techniques, communication aids, sensory aids, and social support tools. The objective is to educate and support caregivers of individuals with autism, promote their social integration, and empower them across various environments. The kit packs comprise various tools, including illustrated communication assistance cards that aid individuals in expressing their needs, sensory aids such as stress balls as well and calming music-playing wireless earphones that aid users in emotional regulation during a sudden trigger. “AutiEase Kit” has a potential for commercialization in terms of its customizable and user-friendly tool kit. It is readily accessible and reasonably priced, catering to individuals and families of diverse socioeconomic backgrounds.